Effects of 6E-oriented STEM practical activities in cultivating middle school students' attitudes toward technology and technological inquiry ability. Issue 1 (2nd January 2020) - Lin, Kuen-Yi; Hsiao, Hsien-Sheng; Williams, P. John; Chen, Yu-Han
ABSTRACT: Background : STEM education has become a focus of research and teaching interest in recent years. However, not all scholars agree on the definition and purpose of STEM education. This paper summarizes related past research and suggests that, according to the requirements of Taiwan's educational environment, STEM education should focus on the cultivation of middle school students' attitudes toward technology and their ability to engage with technological inquiry. Purpose : The purpose of this study is to explore the effects of STEM education on attitudes toward technology and technological inquiry abilities of middle school students, this study used the 6E Learning byDeSIGN™ model proposed by the International Technology and Engineering Educators Association in the US to design a 6E-oriented STEM practical activity. Sample : The sample of the study consisted of 139 seventh-grade students from six different classes who participated in a practical activity related to egg protection devices. Design and methods : To achieve this research purpose, a quasi-experimental design was used, with pre-treatment and post-treatment evaluations of each group. Both the experimental and control groups participated in the activity; however, the experimental group students were guided through the activity using a 6E teaching strategy, whereas the control group students were guided using a problem-solving teaching strategy. Results : The results showed that a 6E teaching strategy had a positive effect on middle school students' attitudes toward technology and technological inquiry abilities, but these effects were not statistically different from the effect on the control group with problem-solving teaching strategy. Conclusions : This study indicates there is no significant advantage in using a 6E process over a problem solving approach. Technology teachers aiming to improve students' attitudes toward technology and their technological inquiry abilities consider refining the 6E-oriented STEM practical activity process, and students may demonstrate better performance in these two areas.